Mycorrhizal symbiosis and local adaptation in Aster amellus: a field transplant experiment - Pánková, Hana; Raabová, Jana; Münzbergová, Zuzana (PloS one, 2014)
Many plant populations have adapted to local soil conditions. However, the role of arbuscular mycorrhizal fungi is often overlooked in this context. Only a few studies have used reciprocal transplant experiments to study the relationships between soil conditions, mycorrhizal colonisation and plant growth. Furthermore, most of the studies were conducted under controlled greenhouse conditions. However, long-term field experiments can provide more realistic insights into this issue. We conducted a five-year field reciprocal transplant experiment to study the relationships between soil conditions, arbuscular mycorrhizal fungi and plant growth in the obligate mycotrophic herb Aster amellus. We conducted this study in two regions in the Czech Republic that differ significantly in their soil nutrient content, namely Czech Karst (region K) and Ceske Stredohori (region S). Plants that originated from region S had significantly higher mycorrhizal colonisation than plants from region K, indicating that the percentage of mycorrhizal colonisation has a genetic basis. We found no evidence of local adaptation in Aster amellus. Instead, plants from region S outperformed the plants from region K in both target regions. Similarly, plants from region S showed more mycorrhizal colonisation in all cases, which was likely driven by the lower nutrient content in the soil from that region. Thus, plant aboveground biomass and mycorrhizal colonisation exhibited corresponding differences between the two target regions and regions of origin. Higher mycorrhizal colonisation in the plants from region with lower soil nutrient content (region S) in both target regions indicates that mycorrhizal colonisation is an adaptive trait. However, lower aboveground biomass in the plants with lower mycorrhizal colonisation suggests that the plants from region K are in fact maladapted by their low inherent mycorrhizal colonization. We conclude that including mycorrhizal symbiosis in local adaptation studies may increase our understanding of the mechanisms by which plants adapt to their environment.
Keywords: Aster Plant; Symbiosis; Aster; kořeny rostlin; půdní mikrobiologie; Czech Republic; mykorhiza; Česká republika; aklimatizace; Mycorrhizae; Plant Roots; Soil Microbiology; Acclimatization; symbióza